2021
DOI: 10.1038/s41587-021-00896-6
|View full text |Cite
|
Sign up to set email alerts
|

Gene signature extraction and cell identity recognition at the single-cell level with Cell-ID

Abstract: The exhaustive exploration of human cell heterogeneity requires the unbiased identification of molecular signatures that can serve as unique cell identity cards for every cell in the body. However, the stochasticity associated with high-throughput single-cell sequencing has made it necessary to use clustering-based computational approaches in which the characterization of cell-type heterogeneity is performed at cellsubpopulation level rather than at full single-cell resolution. We present here Cell-ID, a clust… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
128
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(129 citation statements)
references
References 53 publications
1
128
0
Order By: Relevance
“…23A and S24B). These results were validated by using the independent method of Cell-ID [ 64 ] (Additional file 1 : Supplementary methods and Additional file 3 : Fig. S29).…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…23A and S24B). These results were validated by using the independent method of Cell-ID [ 64 ] (Additional file 1 : Supplementary methods and Additional file 3 : Fig. S29).…”
Section: Resultsmentioning
confidence: 86%
“…S16-S19). Additionally, using the Cell-ID method [ 64 ], we found that 34 GWAS-identified genes score of individual cells were higher detected in CD16+ monocytes and memory CD8+T cells (Additional file 3 : Fig. S20).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, the package CelliD 23 , which provides a convenient and scalable workflow to define single-cell gene signatures, is used to define per-cell gene signatures. Briefly, user-defined variable genes are used to embed the dataset into low dimensional space by multiple correspondence analysis (MCA).…”
Section: Methodsmentioning
confidence: 99%
“…Using SingleR, the authors identified a novel disease-associated macrophage subgroup between monocyte-derived and alveolar macrophages. Cortal et al proposed a clustering-free multivariate statistical method named Cell-ID for gene signature extraction and cell identification (Cortal et al, 2021). Cell-ID first performs a dimensionality reduction on the cell-by-gene expression matrix using the multiple correspondence analysis (MCA).…”
Section: Identification Of Cell Typesmentioning
confidence: 99%